The use of cottonseed oil methyl ester on a diesel engine - ilkilic, C.; Yucesu, H. S. (Taylor & Francis Inc, 2008)
Vegetable oils already have been evaluated as substitutes for diesel fuels. High viscosity of the vegetable oil and its tendency to polymerize within the cylinder were major chemical and physical problems that were encountered. Chemical and physical properties of the raw cotton seed oil were improved by transesterification. In general, the physical and chemical properties and the performance of the cotton seed oil methyl ester was comparable to diesel fuel. The effects of cotton seed oil methyl ester and diesel fuel on a direct-injected, four-stroke, single-cylinder, air-cooled diesel engine performance and exhaust emissions were investigated in this article. Test quantities of cottonseed oil methyl ester of renewable fuels were processed and characterized, and performance and exhaust gas emissions were tested in various injection pressures. In order to determine emission and performance characteristics, the engine was tested with full load varied injection pressure and constant speed. The results show that engine performance using cottonseed oil methyl ester fuel differed little from engine performance and torque with diesel fuel. As to the emissions, there was an approximate 30% reduction in CO and approximate 25% reduction in NOx.
Keywords: alternative fuel; cottonseed oil methyl ester; diesel engine; emissions; performance